Pinky and Rex and the perfect pumpkin - Howe, James; Sweet, Melissa (New York : Atheneum Books for Young Readers, 1998)
When Rex accompanies Pinky and his relatives on their traditional trip to pick and carve pumpkins, she feels left out because of the jealous behavior of Pinky's cousin Abby.
Keywords: Pumpkin; Cousins; Jealousy; Friendship